Cross cultural verbal cues to deception: truth and lies in first and second language forensic interview contexts - Dando, Coral J.; Taylor, Paul J.; Sandham, Alexandra L. (Frontiers in Psychology, 2023)
The verbal deception literature is largely based upon North American and Western European monolingual English speaker interactions. This paper extends this literature by comparing the verbal behaviors of 88 south Asian bilinguals, conversing in either first (Hindi) or second (English) languages, and 48 British monolinguals conversing in English. All participated in a live event following which they were interviewed having been incentivized to be either deceptive or truthful. Event details, complications, verifiable sources, and plausibility ratings were analyzed as a function of veracity, language and culture. Main effects revealed cross cultural similarities in both first and second language interviews whereby all liar’s verbal responses were impoverished and rated as less plausible than truthtellers. However, a series of cross-cultural interactions emerged whereby bi-lingual South Asian truthtellers and liars interviewed in first and second languages exhibited varying patterns of verbal behaviors, differences that have the potential to trigger erroneous assessments in practice. Despite limitations, including concerns centered on the reductionary nature of deception research, our results highlight that while cultural context is important, impoverished, simple verbal accounts should trigger a ‘red flag’ for further attention irrespective of culture or interview language, since the cognitive load typically associated with formulating a deceptive account apparently emerges in a broadly similar manner.